(untitled) (Research, Society and Development, 2025)
This study examines the Irecê Territory (State of Bahia - BA) in the Brazilian semi-arid region, focusing on environmental, productive, social, and institutional dimensions to inform integrated public policies and sustainable development strategies. The semi-arid context presents challenges related to water scarcity, low soil fertility, and socioeconomic vulnerabilities, yet the territory shows potential through strong social organization, cultural diversity, and adaptability of family farmers. A mixed-methods approach was employed, including documentary and secondary data analysis, field research with semi-structured interviews, direct observation, and qualitative and quantitative analysis of socio-environmental indicators. Results highlight environmental degradation mitigated by water management and soil conservation practices, low rainfed crop productivity, and promising initiatives in irrigated horticulture, goat and sheep farming, and agroforestry systems. Social cohesion is significant, although challenges persist regarding gender inequality, youth migration, and access to basic services. Institutional frameworks are fragmented, and the limited role of technical assistance (ATER) hinders innovation and sustainable development. The study concludes that isolated policies are insufficient and recommends integrated territorial governance, productive diversification, support for cooperatives, and efficient water resource management. Findings provide a foundation for future research and policy formulation that balances social equity, environmental conservation, and strengthening of family farming in the Brazilian semi-arid region.